Liver Metastases of Unknown Primary: Malignant Melanoma - Ozgur Bostanci; Kinyas Kartal; Muharrem Battal (Case Reports in Hepatology)
According to the National Cancer Institute’s (NCI) data, the increase in the number of patients diagnosed with malignant melanoma was found to be at a higher rate than the current increase in all other types of cancer (Jemal et al., 2008). Early diagnosis, appropriate surgical treatment, and chemotherapy have positive impacts on the course of the disease but despite these developments on the treatment, current prognosis of metastatic malignant melanoma prognosis is still extremely poor. Life expectancy in patients with metastatic disease is between 2 and 8 months. The 5-year disease-free survival rate is identified in only 5% of the patients (Leong, 2003) (Kirkwood et al., 1996). In this study, we try to report a patient with metastatic malignant melanoma and give recent informations about the liver metastases of malignant melanoma.